Syntax Determinants ad sensum and ad formam in Sentences with a Serial Subject - Zbróg, Piotr (Respectus Philologicus, 2022)
The syntax of the serial subject in contemporary Polish poses many problems, especially in the normative context. Many publications emphasize that a verb predicate should be agreed upon based on real-meaning syntax – regardless of the features of the members of the series and the order (e.g. Stół i / lub / czy taboret stały obok siebie vs. Obok siebie stały stół i / lub / czy taboret), and only exceptionally the form of the personal word may be adapted to the nearest segment. However, as evidenced by empirical studies, such an approach is inconsistent with the actual state of affairs. Only in individual cases does the linguistic custom allow for an almost non-exceptional ad sensum syntax (Mąż i żona siedzieli naprzeciwko), and so many examples illustrating the ad formam syntax can be found (Nie Janek, ale Basia czytała najlepiej). There are even more sentences with a variant adaptation (Siedzą / siedzi naprzeciwko mąż i żona). The article lists all the tested series types that determine the real-meaning and formal-grammatical syntax, and they are formally and structurally characterized. Examples of series illustrating the accommodative variability are given as a kind of cliché. The presented material can be treated as a voice in the discussion on prescriptive comments on the syntax of the serialized subject, formulated in corrective publications.